A genome‐wide association study suggests new evidence for an association of the NADPH Oxidase 4 (NOX4) gene with severe diabetic retinopathy in type 2 diabetes. Issue 7 (4th September 2018) - Meng, Weihua; Shah, Kaanan P.; Pollack, Samuela; Toppila, Iiro; Hebert, Harry L.; McCarthy, Mark I.; Groop, Leif; Ahlqvist, Emma; Lyssenko, Valeriya; Agardh, Elisabet; Daniell, Mark; Kaidonis, Georgia; et al.
Abstract: Purpose: Diabetic retinopathy is the most common eye complication in patients with diabetes. The purpose of this study is to identify genetic factors contributing to severe diabetic retinopathy. Methods: A genome‐wide association approach was applied. In the Genetics of Diabetes Audit and Research in Tayside Scotland (GoDARTS) datasets, cases of severe diabetic retinopathy were defined as type 2 diabetic patients who were ever graded as having severe background retinopathy (Level R3) or proliferative retinopathy (Level R4) in at least one eye according to the Scottish Diabetic Retinopathy Grading Scheme or who were once treated by laser photocoagulation. Controls were diabetic individuals whose longitudinal retinopathy screening records were either normal (Level R0) or only with mild background retinopathy (Level R1) in both eyes. Significant Single Nucleotide Polymorphisms (SNPs) were taken forward for meta‐analysis using multiple Caucasian cohorts. Results: Five hundred and sixty cases of type 2 diabetes with severe diabetic retinopathy and 4, 106 controls were identified in the GoDARTS cohort. We revealed that rs3913535 in the NADPH Oxidase 4 ( NOX4 ) gene reached a p value of 4.05 × 10 −9 . Two nearby SNPs, rs10765219 and rs11018670 also showed promising p values (p values = 7.41 × 10 −8 and 1.23 × 10 −8, respectively). In the meta‐analysis using multiple Caucasian cohorts (excluding GoDARTS), rs10765219 and rs11018670 showed associations for diabetic retinopathy (p = 0.003 and 0.007, respectively), while the p value of rs3913535 was not significant (p = 0.429). Conclusion: This genome‐wide association study of severe diabetic retinopathy suggests new evidence for the involvement of the NOX4 gene.